Effect of precision nitrogen management on growth, yield and yield components of rice in Khumaltar, Lalitpur - Kaduwal, Sangita; Timalsina, Himal Prasad; Neupane, Reshama; Battarai, Rajendra Kumar; Chaulagain, Bhimsen; Ghimire, Prakash (Agronomy Journal of Nepal, 2025)
Enhancing the nitrogen use efficiency (NUE) is essential for sustainable rice production, especially in areas where general fertilizer recommendations don’t take field-specific variability into account. Rice (var. NR11105) was the plant material of a two-year field experiment (2023 and 2024) at the National Agronomy Research Centre, Khumaltar, Nepal, to assess the impact of precision nitrogen management practices on rice growth and yield parameters. Three replications of the experiment were set up in a randomized complete block design. N omission (control), farmer practices, the recommended fertilizer dose (RDF: 100:30:30 kg N:P₂O₅: K₂O ha⁻¹), N management based on Leaf Color Chart (LCC), SPAD meter-based N management, NDVI-based N management, and Nutrient Expert®-Site Specific Nutrient Management (NE-SSNM) were among the treatments. Pooled analysis showed significant treatment effects of treatments were found for tiller number, grains per panicle, thousand-grain weight, sterility %, biomass yield, and grain yield. While SPAD (5.49 t ha⁻¹), RDF (5.47 t ha⁻¹), and LCC (5.19 t ha⁻¹) were statistically similar, NDVI- and NE-SSNM-based treatments yielded the maximum grain production (5.70 t ha⁻¹). The control (1.78 t ha⁻¹) and farmer practice (3.38 t ha⁻¹) yields were the lowest. Comparing precision-based N management to traditional methods, the former improved biomass accumulation and decreased the sterility percentage. The yield improvement with NE-SSNM and NDVI was 4.2% more than that under RDF. The results show that N management strategies based on sensors and decision assistance improve rice productivity and nitrogen use efficiency more than general advice. The sustainable intensification of rice systems in Nepal and other agro-ecological settings can be supported by the use of site-specific nutrient management techniques.